Recommendations for Diagnosis and Treatment of Children with Transient Abnormal Myelopoiesis (TAM) and Myeloid Leukemia in Down Syndrome (ML-DS) - Al-Kershi, Sina; Golnik, Richard; Flasinski, Marius; Waack, Katharina; Rasche, Mareike; Creutzig, Ursula; Dworzak, Michael; Reinhardt, Dirk; Klusmann, Jan-Henning (Klinische Pädiatrie, 2021)
Children with Down syndrome are at a high risk of developing transient abnormal myelopoiesis (TAM; synonym: TMD) or myeloid leukemia (ML-DS). While most patients with TAM are asymptomatic and go into spontaneous remission without a need for therapy, around 20% of patients die within the first six months due to TAM-related complications. Another 20–30% of patients progress from TAM to ML-DS. ML-DS patients are particularly vulnerable to therapy-associated toxicity, but the prognosis of relapsed ML-DS is extremely poor – thus, ML-DS therapy schemata must strive for a balance between appropriate efficacy (to avoid relapses) and treatment-related toxicity. This guideline presents diagnostic and therapeutic strategies for TAM and ML-DS based on the experience and results of previous clinical studies from the BFM working group, which have helped reduce the risk of early death in symptomatic TAM patients using low-dose cytarabine, and which have achieved excellent cure rates for ML-DS using intensity-reduced treatment protocols.
Keywords: down syndrome; trisomy 21; leukemia; transient abnormal myelopoiesis; treatment recommendation; guideline